A detailed exploration of intermolecular interactions in 4-(4-dimethylaminobenzylideneamino)-N-(5-methyl-3-isoxazolyl) benzenesulfonamide and related Schiff bases: Crystal structure, spectral studies, DFT methods, Pixel energies and Hirshfeld surface analysis - Gil, Diego M. (2017)
The Schiff base of the title has been synthesized and its crystal structure determined by single-crystal X-ray diffraction. The compound was characterized by IR, Raman, 1H NMR, 13C NMR and electronic absorption spectra. DFT calculations provide the quantumchemical basis for the observed molecular conformation. A study of intermolecular interactions of the title compound is comparedwith seven other closely related structures and reveals that molecules in most of the compounds are linked by a cooperative effect of strong and weak hydrogen bonds, C\\H…π, and π…π stacking interactions, and also lp…π contacts. Lattice energy calculations indicate that the dispersion component is the major contribution, with the coulombic term playing a significant role in the total energy. Interaction energies for molecular pairs involving N\\H···N bonds indicate a dominant contribution to packing stabilization coming from coulomb component. Hirshfeld surfaces and 2D–fingerprint plots allowed us to visualize different intermolecular contacts and its relative contributions to total surface in each compound. The analysis of electrostatic potential (ESP) maps correlates well with the computed energies providing evidences on the dominant electrostatic nature of N\\H···N and N\\H···O interactions.